Phages as Therapeutic Tools to Control Major Foodborne Pathogens: Campylobacter and Salmonella - Carvalho, Carla M.; Santos, Sílvio B.; Kropinski, Andrew M.; Ferreira, Eugénio C.; Azeredo, Joana (IntechOpen, 2012)
None